Proceedings of the Workshop on Experiences with Modern Rice Cultivation in Bangladesh, 8-10 June 1993. - Workshop on Experiences with Modern Rice Cultivation in Bangladesh 1993 : Bangladesh Rice Research Institute); Bangladesh Rice Research Institute; Bangladesh. Department of Agriculture Extension (Gazipur : Bangladesh Rice Research Institute, 1994)
Papers presented at the 16th national workshop.
Includes Index.
"Jointly sponsored by Bangladesh Rice Research Institute and Department of Agriculture Extension."
Includes bibliographical references (p. 133).
Includes passages in Bengali.
Keywords: Rice -- Bangladesh -- Congresses; Rice -- Varieties -- Bangladesh -- Congresses